Asas Kepercayaan Dalam Transaksi Jual Beli Online (PerspektifKUHPerdata dan UU No 11 Tahun 2008 Tentang Informasi DanTransaksi Elektronik) - Megandari, Galih Yogi, Shallman Al Farizy, S.H.,M.Kn, Darsono, S.H.,M.H (2015)
It examines the legal research and answer the problems concerning the implementation of the principle of trust in the buying and selling through electronic media but it is also about the validity of the sale and purchase through electronic media in the perspective of Law No. 11 Year 2008 on Information and Electronic Transactions. In this paper uses normative legal research. Research conducted by the authors is descriptive. Date collection techniques in this study using literature study and field study Based on the study concluded that the implementation of the sale and purchase transactions through electronic conducted by researchers can not be done by everyone. There is a positive relationship between trust in the seller to the buyer in the purchase decision over the internet. There is the application of legal principles in the implementation of electronic transactions through the purchase made by the seller (merchant) and the buyer or consumer. The principles are applied in the implementation of electronic transactions through the purchase is the principle of good faith, the principle of trust, personality principle, the principle of freedom of contract, konsensualisme principle, the principle of binding force, and the principle of legal certainty. The validity of the parties to a transaction that the consumer is a legitimate customer to a company organizing specific payment system or credit card as Kualiva and Stand Card and the validity of the existence of the merchant itself. While the validity of the transaction data is transaction data that the recipient is believed to be made by the parties claiming to make it (usually the creator of this data requires the signature). It also includes a guarantee that the signature on the document can not be falsified or altered .